Fibroadenoma vulvar: reporte de un caso y revisión de la literatura (2014)
A fibroadenoma is a benign lesion usually found in the breast. However, it is rare to find it in the vulvar area. It is clinically presented as an asymptomatic, subcutaneous, unilateral lump, of different sizes and with multiple diagnosis, therefore the histopathologic exam is needed to give a diagnosis. Histopathologically, these are biphasic fibroepithelial tumors composed of a glandular epithelial component and a stromal component, similar to those found in the breast. The histogenesis of this type of injuries is unknown. The treatment for this type of injury is the resection, giving an excellent prognostic. We report a case of 42 years-old patient without diseases, who shows a asymptomatic lesion in the vulvar area is presented.